2023
DOI: 10.3390/app13116804
|View full text |Cite
|
Sign up to set email alerts
|

Single vs. Multi-Label: The Issues, Challenges and Insights of Contemporary Classification Schemes

Abstract: Over the decades, a tremendous increase has been witnessed in the production of documents available in digital form. The increased production of documents has gained so much momentum that their rate of production jumps two-fold every five years. These articles are searched over the internet via search engines, digital libraries, and citation indexes. However, the retrieval of relevant research papers for user queries is still a pipedream. This is because scientific documents are not indexed based on some subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In that research, we suggested an electronic data exchange (EDI) framework for smart healthcare in the context of smart cities supported by blockchain technology. To enable secure and effective EHR maintenance and exchange among multiple entities in the smart healthcare ecosystem, the proposed platform makes use of the benefits of blockchain technology [56][57][58][59][60]. Four essential parts made up the proposed framework: (1) Personal servers are local storage devices that store and encrypt EHR and communicate with cloud servers.…”
Section: Discussionmentioning
confidence: 99%
“…In that research, we suggested an electronic data exchange (EDI) framework for smart healthcare in the context of smart cities supported by blockchain technology. To enable secure and effective EHR maintenance and exchange among multiple entities in the smart healthcare ecosystem, the proposed platform makes use of the benefits of blockchain technology [56][57][58][59][60]. Four essential parts made up the proposed framework: (1) Personal servers are local storage devices that store and encrypt EHR and communicate with cloud servers.…”
Section: Discussionmentioning
confidence: 99%
“…This section provides the statistical analysis of the dataset which will eventually be helpful during the modelling, designing and analysis phase [33][34][35][36][37]. That mainly includes:…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the loss rate stands for the total errors or the variance between the predicted and the actual values. Using a variety of metrics will significantly help in defining the performance of the proposed study [51][52][53][54][55][56]. The Equations (1)-( 4) of the previously mentioned measures are seen below.…”
Section: Performance Measurementioning
confidence: 99%